Optimization of heterogeneous VRP model by considering recharging station using mixed integer programming - Sundari Retno Andani; Muhammad Zarlis; Herman Mawengkang; Sutarman Sutarman (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2023)
Transportation activities require substantial costs: drivers, fuel, vehicle maintenance, vehicle and equipment procurement capital, and administrative activities. In the vehicle routing problem (VRP), all vehicles have the same load capacity. But in reality, the company has vehicles with different abilities. The heterogeneous vehicle routing problem (HVRP) is a variant of VRP. Transportation is a source of pollution. Therefore, electric vehicles are starting to replace fossil fuel vehicles. However, a few electric vehicle recharging stations remain, especially in Indonesia. Consequently, the authors build a heterogeneous vehicle routing problem model by considering the filling station using mixed integer programming. This research aims to create a model by determining distribution routes with minimum costs from several capacities of electric-powered freight fleets with different capabilities by considering refilling stations. Research contributions realize the transition towards sustainable energy, one of the priority issues in Indonesia’s G20 presidency.